Effect of agglomeration on the selective distribution of nanoparticles in binary polymer blends. (October 2021) - Zhang, Haimo; Zuo, Min; Zhang, Xinyue; Shi, Xuanyu; Yang, Li; Sun, Shihao; Zhong, Jun; Song, Yihu; Zheng, Qiang
Highlights: The dispersion form of particles affects their selective location. Isolated particles are easier to distribute at the interface than aggregates. Wetting coefficient requires additional consideration of roughness. Abstract: The location of isolated SiO2 nanoparticles (NPs) grafted with silane or poly(methyl methacrylate) (PMMA) brushes and their agglomerates in a phase-separated PMMA/poly(styrene-acrylonitrile) (SAN) blend is investigated. The isolated NPs can be selectively distributed at the interface of PMMA/SAN blend, while their agglomerates are selectively distributed in one phase of blend matrix. Without the interference of uneven modification and kinetic factors, such abnormal thermodynamic distribution phenomenon can be well explained with the introduction of Wenzel's roughness and the wetting coefficient of NPs agglomerates might be remarkably amplified relative to that of isolated NPs, resulting in their different locations of isolated brush NPs and their agglomerates in the blend matrix. The thorough understanding of the entropic contribution to the selective distribution of isolated brush NPs and their agglomerates in the blend matrix may help us prepare nanocomposites with the desired microstructure.